Critical range of soil organic carbon in southern Europe lands under desertification risk. (1st June 2021) - Grilli, Eleonora; Carvalho, Sílvia C.P.; Chiti, Tommaso; Coppola, Elio; D'Ascoli, Rosaria; La Mantia, Tommaso; Marzaioli, Rossana; Mastrocicco, Micòl; Pulido, Fernando; Rutigliano, Flora Angela; Quatrini, Paola; Castaldi, Simona
Abstract: Soil quality is fundamental for ecosystem long term functionality, productivity and resilience to current climatic changes. Despite its importance, soil is lost and degraded at dramatic rates worldwide. In Europe, the Mediterranean areas are a hotspot for soil erosion and land degradation due to a combination of climatic conditions, soils, geomorphology and anthropic pressure. Soil organic carbon (SOC) is considered a key indicator of soil quality as it relates to other fundamental soil functions supporting crucial ecosystem services. In the present study, the functional relationships among SOC and other important soil properties were investigated in the topsoil of 38 sites under different land cover and management, distributed over three Mediterranean regions under strong desertification risk, with the final aim to define critical SOC ranges for fast loss of important soil functionalities. The study sites belonged to private and public landowners seeking to adopt sustainable land management practices to support ecosystem sustainability and productivity of their land. Data showed a very clear relationship between SOC concentrations and the other analyzed soil properties: total nitrogen, bulk density, cation exchange capacity, available water capacity, microbial biomass, C fractions associated to particulate organic matter and to the mineral soil component and indirectly with net N mineralization. Below 20 g SOC kg −1, additional changes of SOC concentrations resulted in a steep variation of all the analyzed soil indicators, an order of magnitude higher than the changes occurring between 50 and 100 g SOC kg −1 and 3–4 times the changes observed at 20–50 g SOC kg −1 . About half of the study sites showed average SOC concentration of the topsoil centimetres <20 g SOC kg −1 . For these areas the level of SOC might hence be considered critical and immediate and effective recovery management plans are needed to avoid complete land degradation in the next future. Highlights: SOC was an important indicator of soil quality in areas under desertification risk. A critical limit of 20 g SOC kg −1 was found for soil quality in the analyzed areas. Soil properties rapidly changed for a variation of 1% SOC below critical limit. MAOC represented most of the organic C pool <50 g SOC kg −1 .